2019
DOI: 10.1182/bloodadvances.2018025502
|View full text |Cite
|
Sign up to set email alerts
|

Mixed chimerism established by hematopoietic stem cell transplantation is maintained by host and donor T regulatory cells

Abstract: Transplantation is an effective treatment of many clinical disorders, but the mechanisms that regulate immunological tolerance are uncertain and remain central to improving patient outcome. Hemopoietic stem cell transplantation (SCT) often establishes “mixed chimerism” in which immune cells from both the donor and patient coexist in vivo in a setting of immunological tolerance. We studied immune function in 69 patients within 2 months following SCT; 37 were fully donor and 32 displayed mixed chimerism. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…However, considering these results it would seem plausible that IMC several months prior to relapse does not reflect circulating leukemic cells but rather a reduced alloreactivity of the graft gradually paving the way for recurrence of the malignant clone. This is supported by a recent study showing an increased proportion of T regulatory cells in patients with mixed compared to full donor chimerism . Thus, highly sensitive, sequential measurements of chimerism could provide information on the potency of the graft‐versus‐leukemia effect, with the potential of guiding interventions aimed at strengthening this effect …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, considering these results it would seem plausible that IMC several months prior to relapse does not reflect circulating leukemic cells but rather a reduced alloreactivity of the graft gradually paving the way for recurrence of the malignant clone. This is supported by a recent study showing an increased proportion of T regulatory cells in patients with mixed compared to full donor chimerism . Thus, highly sensitive, sequential measurements of chimerism could provide information on the potency of the graft‐versus‐leukemia effect, with the potential of guiding interventions aimed at strengthening this effect …”
Section: Discussionsupporting
confidence: 88%
“…This is supported by a recent study showing an increased proportion of T regulatory cells in patients with mixed compared to full donor chimerism. 56 Thus, highly sensitive, sequential measurements of chimerism could provide information on the potency of the graftversus-leukemia effect, with the potential of guiding interventions aimed at strengthening this effect. 33 We next tested whether RQ-PCR chimerism status during the first 90 days post-HCT was associated with relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that developing mixed chimerism post-HCT in non-malignant disease is associated with a lower incidence of aGvHD and cGvHD and among patients with mixed chimerism, cGvHD is associated with a more frequent evolution toward complete chimerism ( 72 ). The proportion of Treg cells is increased in patients with mixed chimerism after SCT and acts to suppress the alloreactive immune response ( 73 ). In non-malignant diseases, especially those undergoing reduced intensity conditioning resulting in dynamic chimera states, interventions to increase Tregs may stabilize mixed chimerism and lead to lower rates of cGvHD.…”
Section: T Cell Immune Dysregulationmentioning
confidence: 99%
“…These findings suggest that the long-term graft survival might be due to the ability of the transferred T regs to induce infectious tolerance. Recent studies show that both the donor and recipient T regs contribute to suppress the alloreactive responses after HCT ( 105 , 117 , 118 ). The integration of T reg therapy into combined organ or islet transplantation is therefore a potentially non-toxic method for improving tolerance induction and establishing mixed hematopoietic chimerism.…”
Section: Critical Role Of Tregs In Mixed Chimerism and Graft Tolerancmentioning
confidence: 99%